2022
DOI: 10.1002/ejhf.2565
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial volume index and outcome after transcatheter edge‐to‐edge valve repair for secondary mitral regurgitation

Abstract: To investigate the role of left atrial volume index (LAVi) in patients with secondary mitral regurgitation (SMR) undergoing transcatheter edge-to-edge mitral valve repair (TEER).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Residual MR 1+ after MitraClip was associated with reduced risk of 1 year mortality, compared with residual MR 2+ and 3/4+ 188,189 . LA enlargement is a strong and independent predictor of adverse long‐term outcome after M‐TEER 77,190 . Among 221 patients with HFrEF and MR ≥ 3+ successfully treated with M‐TEER, 40% had an improvement in right ventricular (RV) function, and this finding was independently associated with lower risk of death or heart transplantation (HTx) [hazard ratio (HR) 0.52; 95% confidence interval (CI) 0.29–0.94; P = 0.030] 191 .…”
Section: Treatment Of Heart Failure With Reduced Ejection Fractionmentioning
confidence: 99%
“…Residual MR 1+ after MitraClip was associated with reduced risk of 1 year mortality, compared with residual MR 2+ and 3/4+ 188,189 . LA enlargement is a strong and independent predictor of adverse long‐term outcome after M‐TEER 77,190 . Among 221 patients with HFrEF and MR ≥ 3+ successfully treated with M‐TEER, 40% had an improvement in right ventricular (RV) function, and this finding was independently associated with lower risk of death or heart transplantation (HTx) [hazard ratio (HR) 0.52; 95% confidence interval (CI) 0.29–0.94; P = 0.030] 191 .…”
Section: Treatment Of Heart Failure With Reduced Ejection Fractionmentioning
confidence: 99%
“…Iliadis et al showed that the symptomatic benefit of the procedure is high regardless of baseline LAVi values. 14 The left atrial strain findings are thought-provoking. PMR patients had a significantly higher magnitude of left atrial strain at baseline compared with SMR regardless of phase, likely reflecting the underlying myocardial disease seen in SMR.…”
Section: Discussionmentioning
confidence: 99%
“…Our study population was characterized by baseline high LAVi values and no significant changes in LAVi were observed after the procedure. Iliadis et al showed that the symptomatic benefit of the procedure is high regardless of baseline LAVi values 14 …”
Section: Discussionmentioning
confidence: 99%
“…HF phenotypes of advanced disease [i.e. left atrium enlargement and RV dysfunction] represent independent predictors of adverse long-term outcome after M-TEER 108–110 . An improvement in RV function at early follow-up (median time 4 months) was observed in almost 40% of patients undergoing successful M-TEER and was associated with lower risk of both death/heart transplantation and HF hospitalization 110 .…”
Section: Comorbidities and Special Conditionsmentioning
confidence: 99%